Sustainable Development Strategy of Large Pelagic Fishery In South Halmahera District - Abdullah, Rommy M.; Taeran, Imran (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2021)
This study aims to measure and determine the sustainability status of large pelagic fisheries from a sustainability perspective according to ecological, economic, social, technological, and legal/institutional dimensions and formulate appropriate strategies in order to support the sustainability of large pelagic fisheries, according to ecological, economic, social, technological, and legal/institutional dimensions in South Halmahera Regency. The method used is a survey method and quantitative descriptive with analytical tools, RAPFISH and AHP analysis. The results of the analysis show that the sustainability of the ecological and legal dimensions and institutions of large pelagic fisheries have sustainability indexes of 64.30 and 63.71, respectively. Meanwhile, the economic, social and technological dimensions have a sustainability index of 45.41, 49.31 and 42.29, respectively. The formulation of the strategy for developing large pelagic fisheries in South Halmahera district is increasing the welfare of fishing actors, improving the production marketing system, developing environmentally friendly fishing technology, increasing productivity and efficiency of sustainable fishing, and developing legal and institutional capacity for pelagic fisheries.